The prevalence and risk factors of postpartum depression among urban, low-income mothers: A retrospective study - Singh, Sunita; Kumari, Smita (Orapuh Journal, 2024)
IntroductionParticularly in the metropolitan areas of low socioeconomic status where inequalities in mothers' mental health are most prominent, Postpartum Depression (PPD) poses a severe threat to public health.PurposeThis retrospective study aimed to determine the prevalence of PPD and its risk variables among urban, low-income mothers.MethodsWe looked back at the medical histories of 200 women at the Department of Obstetrics and Gynaecology, Patna Medical College and Hospital (PMCH), Bihar, India, who had recently given birth in poor cities. PPD and risk factor information were gathered when eligibility criteria were established. Estimating prevalence and identifying risk factors were among the statistical analyses performed.ResultsA high prevalence of PPD (32.5%) was found in the study, highlighting the significant burden of PPD in this community. A lack of social support (51.2%), exposure to high environmental stressors (55.6%), a history of mental health disorders (48.9%), and being younger (38.2% in the 18-25 years age bracket) were the significant risk factors of PPD in the study population. These results are important because they shed light on the unique difficulties experienced by postpartum patients living in urban areas with low incomes.ConclusionThis research emphasises the critical importance of implementing specific programmes to reduce PPD in low-income metropolitan areas. Early screening, intervention, and support programmes should be adopted to address the risk factors identified. To promote a more accepting atmosphere for mothers' mental health, healthcare policies should emphasise mental health treatments and reduce stigma.